Long-term impact of fertigation with treated sewage effluent on the physical soil quality - Coelho, Anderson Prates [UNESP]; Silva, Matheus Flavio da [UNESP]; Faria, Rogério Teixeira de [UNESP]; Fernandes, Carolina [UNESP]; Dantas, Geffson de Figueiredo [UNESP]; Santos, Gilmar Oliveira (Elsevier, 2020)
In agriculture, wastewater is used as an alternative source to meet the water and nutritional requirements of plants. However, long-term application of wastewater may degrade soil attributes. This study aimed to evaluate the soil physical quality of Oxisol fertigated with treated sewage effluent (TSE). The experiment was conducted in an area under TSE application for 4 years in Oxisol (625 g kg−1 clay) cultivated with Urochloa brizantha. The treatments consisted of six levels of TSE in irrigation depth, 0%, 11%, 31%, 60%, 87%, and 100%, with four repetitions. Undisturbed and disturbed soils samples were collected in three layers (0.00–0.10 m; 0.10–0.20 m, and 0.20–0.30 m). Aggregation, porosity and water infiltration attributes were evaluated. This work concludes a long-term study on the effects of TSE application on soil properties and on the Urochloa brizantha crop. In other works, carried out in the experimental area of the present study, it was found that TSE fertigation increases the yield and quality of Urochloa brizantha, increases soil fertility and does not lead to soil heavy metal contamination. We note the TSE fertigation does not change the aggregation, porosity, water infiltration rate and organic carbon content in the soil. Irrigation with TSE is recommended in areas with clayey soil and those cultivated with perennial grasses as it does not cause any damage to the physical quality of the soil. Thus, the TSE fertigation can be used on many crops as a source of water and nutrients, reducing the environmental contamination potential.
Keywords: Environmental sustainability; Soil aggregation; Urochloa brizantha; Wastewater fertigation; Water infiltration rate